2020
DOI: 10.1111/ajt.16304
|View full text |Cite
|
Sign up to set email alerts
|

Lung transplantation during the COVID-19 pandemic: Safely navigating the new “normal”

Abstract: In the United States, an overall national decline in organ transplants has accompanied the substantial burden of COVID‐19. Amidst significant regional variations in COVID‐19, lung transplantation (LTx) remains a critical life‐saving operation. Our LTx practice during the early pandemic may provide a blueprint for managing LTx in an era of continued community prevalence. Patients who underwent LTx at our institution between March 1 and May 20, 2020 were included. Recipient, operative, and donor characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
(27 reference statements)
0
12
0
3
Order By: Relevance
“…The reasons behind these differences are unclear, however a possible explanation may be that shutdowns or severe restrictions of certain centers led to centers that did not restrict lung transplantation being able to transplant patients with lower LAS. Notably, a report from Duke University, one of the busiest lung transplant programs in the country, did not find a significant difference in LAS score in their cohort of lung transplants early in the pandemic 12 . However, this change deserves further attention as it may highlight potential opportunities for patients with lower LAS in the future to receive lung transplantation.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The reasons behind these differences are unclear, however a possible explanation may be that shutdowns or severe restrictions of certain centers led to centers that did not restrict lung transplantation being able to transplant patients with lower LAS. Notably, a report from Duke University, one of the busiest lung transplant programs in the country, did not find a significant difference in LAS score in their cohort of lung transplants early in the pandemic 12 . However, this change deserves further attention as it may highlight potential opportunities for patients with lower LAS in the future to receive lung transplantation.…”
Section: Discussionmentioning
confidence: 98%
“…5,[8][9][10] As the pandemic has progressed, single centers have provided data demonstrating that transplantation of all organs can be safely done with respect to recipient outcomes. 11,12 Furthermore, centers have described how planning of ICU resources, risk stratification at a donor and recipient level as well as rigorous and efficient testing allows for safe transplantation. 13 Notably, Goff et al analyzed the SRTR data over the same time frame and demonstrated that while there was an initial decrease in transplants, the volumes have since increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In response, the COVID-19 pandemic has propelled the development of specific approaches to COVID-19 for perioperative LTx management that balance concerns regarding waitlist mortality with the goal of maintaining successful outcomes. 15…”
Section: Lung Transplantationmentioning
confidence: 99%